Romania : Financial Sector Stability Assessment. (IMF Staff Country Reports; Country Report ;, 2010)
This paper discusses key findings of the financial sector stability assessment for Romania. The assessment reveals that in recent years, Romania's financial sector regulatory authorities have made significant progress in adopting international best practices, including through transposition of European Union directives, as well as through implementation of many of the recommendations of the 2003 Financial Sector Assessment Program. In the current circumstances, a number of measures to strengthen the crisis management and safety net framework are recommended.